Advancing the regional commons in the new East Asia - Siriphō̜n Watchawankhu; Ho, Kong-Chong 1955-; Yoshida, Osamu 1960- (Politics in Asia, 2016)
Advancing the Regional Commons in the New East Asia highlights a number of interests which members of ASEAN and Plus Three countries collectively recognize. This set of common interests includes not only economic development but also social development. Written by nationals in their respective countries, the different chapters in this volume highlights the different foundations for such common interests and these reflect the different constructive ways in which ASEAN and Plus Three countries come to see a multi-strand cooperative partnership.